2012
DOI: 10.1258/td.2012.120023
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury in dengue fever using Acute Kidney Injury Network criteria: incidence and risk factors

Abstract: The aim of this study was to assess incidence and risk factors for acute kidney injury (AKI) in patients with dengue fever (DF). A total of 223 patients (males, 130; females, 93; mean age, 26.2 ± 18.2 years) from a tertiary care centre in southern India were retrospectively analysed. Acute renal failure (ARF) developed in 24 (10.8%) patients. Based on the Acute Kidney Injury Network (AKIN) criteria, the results revealed that: 12 (5.4%) had mild AKI; seven (3.1%) had moderate AKI; and five (2.2%) had severe AKI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
70
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(82 citation statements)
references
References 9 publications
7
70
4
1
Order By: Relevance
“…In this regard, when the AKIN classification was evaluated, the incidence of AKI ranged from 10.8% to 13.3%5 6 while, with CD, the incidence varied between 0.9% and 3.3% 3 4. We found two studies evaluating the incidence of AKI using the RIFLE criteria that reported a much higher incidence than our study 13 14.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…In this regard, when the AKIN classification was evaluated, the incidence of AKI ranged from 10.8% to 13.3%5 6 while, with CD, the incidence varied between 0.9% and 3.3% 3 4. We found two studies evaluating the incidence of AKI using the RIFLE criteria that reported a much higher incidence than our study 13 14.…”
Section: Discussioncontrasting
confidence: 46%
“…The probability of developing AKI in dengue infection varies from 0.9% to 13.3% according to the diagnostic criteria adopted and the severity of the dengue infection—that is, dengue fever (DF), dengue haemorrhagic fever (DHF) or dengue shock syndrome (DSS) 3–6. The reported incidence of AKI is 0.9%3 and 3.3%4 in DHF/DSS, while the incidence of AKI has been reported to be 10.8%5 and 13.3%6 in all types of dengue infection, irrespective of severity. The development of AKI has a significant impact on the outcome of patients with dengue infection, with mortality estimated at 11.3–64% and a longer hospital stay 3 4 6.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging data suggest hospital survivors of critical illness complicated by AKI have a greater than threefold increased risk for end stage kidney disease (ESKD) over the subsequent decade when compared with matched controls (10). Incomplete or partial recovery of kidney function following AKI is likely to become an increasingly recognized problem, and data suggest these patients also have a lower rate of survival and a higher risk of progression to ESKD (11,12). In our study, recovery of renal function was noted in 85% of patients.…”
Section: Malleshappa P Et Al : Spectrum Of Acute Kidney Injury and Itmentioning
confidence: 46%
“…Acute cardiorenal syndrome where in Acute cardiogenic shock and acutely decompensated congestive heart failure leads to acute kidney injury was the fourth (12.3%) leading cause of AKI in our study. Dengue fever related AKI comprise 10.8% of AKI in a recent study from south India (12). In our study population, Denguerelated AKI contributed to 6.2% of the cases.…”
Section: Malleshappa P Et Al : Spectrum Of Acute Kidney Injury and Itmentioning
confidence: 54%